The Treatment of Primary Angle-Closure Glaucoma with Cataract: A Systematic Review and Meta-Analysis of Randomized Controlled Trails - Jia Xie; Wan Li; Bo Han (Ophthalmology and Therapy, 2022)
Abstract Background Currently, there is no generally approved surgical treatment for patients with primary angle-closure glaucoma (PACG) and co-existing cataracts. The aim of this systematic review and meta-analysis was to compare the efficacy and safety of phacoemulsification and phacotrabeculectomy in PACG patients with cataract. Methods Diverse databases were searched, including PubMed, MEDLINE, EMBASE, Cochrane Library, Chinese Journal Full-text Database (CNKI), Wanfang database, and China Science and Technology Journal Database, for randomized controlled trials (RCTs) on phacoemulsification and phacotrabeculectomy for the treatment of PACG published up to 30 June 2021. ReviewManager (RevMan) version 5.4 software was used for the meta-analysis, and the effective quantity of measurement data was measured by the mean difference (MD) and 95% confidence interval (CI). The effect of counting data was measured by odds ratio (OR). Results Our search of the databases identified 14 RCTs that satisfied the search criteria. Meta-analysis of these 14 RCTs showed that at the 1 month postoperative follow-up, intraocular pressure (IOP) of patients in the phacoemulsification group was higher than that of patients in the phacotrabeculectomy group (MD 2.04, 95% CI 1.42–2.65; P < 0.00001). However, the postoperative IOP was not significantly different between the two groups at the 3, 6, and 12 months postoperative follow-ups (P = 0.52, P = 0.51, and P = 0.05, respectively). More medications for IOP reduction were required by patients in the phacoemulsification group compared with those in the phacotrabeculectomy group at 3 months postoperation (MD 0.76, 95% CI 0.33–1.18; P = 0.0005), 6 months postoperation (MD 0.66, 95% CI 0.15–1.18; P = 0.01), and 12 months postoperation (MD 0.76, 95% CI 0.22–1.30; P = 0.006). Patients in the phacoemulsification group obtained better best corrected visual acuity (BCVA) than those in the phacotrabeculectomy group (MD − 0.17, 95% CI − 0.34 to − 0.01; P = 0.04) at 3 months postoperation, but there was no significant difference in BCVA between the two groups at 6 and 12 months postoperation (P = 0.33 and P = 0.56, respectively). The deepened anterior chamber was more obvious in patients in the phacoemulsification group versus those in the phacotrabeculectomy group (MD 0.61, 95% CI 0.03–1.18; P = 0.04). Patients in the phacoemulsification group experienced fewer postoperative complications than those in the phacotrabeculectomy group (OR 0.27, 95% CI 0.17–0.42; P < 0.00001). Conclusion Our results provide evidence that phacotrabeculectomy has advantages over phacoemulsification for the treatment of PACG in terms of better IOP and reduced medication need during the early stage post surgery. However, in terms of the complication risk, phacoemulsification is the more secure treatment option.